Математична модель масообмінних процесів первапораційного очищення води - Буртна, Інесса Анатоліївна; Ружинська, Людмила Іванівна; Руденко, Леся Сергіївна (НТУ "ХПІ", 2016)
З розвитком сучасного суспільства зростає інтерес до енергоощадних та безвідходних технологій. Одними з таких є мембранні процеси, а саме первапорація, яка дозволяє розділяти суміші на окремі "чисті" компоненти. В даній статті представлено аналіз особливостей масообмінних процесів при первапораційному розділенні рідких органічних сумішей. Запропонована математична модель процесу, та сформульовані початкові і граничні умови. Показано,що вирішення даної математичної моделі дозволяє знайти такий технологічний режим, при якому максимально реалізуються можливості мембрани, а енергетичні затрати на процес є мінімальними.

The current state of the problem, namely the existing mathematical model of membrane processes had been analyzed. After analysis of features of pervaporation purification process the mathematical model was formulated. The mathematical model describes the pervaporation of organic liquid component through the non-porous membrane in a circular cross section channel. Initial and boundary conditions for this mathematical model had been recorded. Without these conditions the solution is impossible. Solution of the equations of mathematical model with the initial and boundary conditions allows to determine the concentration distribution of liquid flow which passes the membrane, and also though the membrane thickness depending on the size of the membrane, the modes of motion of initial and gas-vapor mixture, the concentration of organic impurities in initial and gas vapor mixture. A mathematical model allows to finding a mode of operating of unit at which completely realized possibilities of membranes and minimized the cost of liquid heating and condensate cooling.
Mathematical model of mass transfer processes of pervaporation water purification
Keywords: мембранні процеси; розділення сумішей; водно-органічна суміш; membrane processes; division of mixtures; water-organic mixture